Epistemologi dan Kegunaan Ilmu Ma’ani Al-Hadits dalam Memahami Makna dan Konteks Sabda Nabi Saw. - Fatmal, Abd. Bashir; Mosiba, Risna; Ahmad, La Ode Ismail; Hafid, Erwin (Journal of Qur’an and Hadith, 2026)
Ma’ānī al-hadīṡ is a branch of hadith studies that plays a fundamental role in uncovering the meanings, intentions, and contextual dimensions of the Prophet Muḥammad’s traditions. Amid the growing tendency toward textual and literal interpretations of hadith, an epistemological examination of this discipline has become increasingly important to produce comprehensive and contextual understandings. This study aims to analyze the epistemological foundations, position, and significance of ma’ānī al-hadīṡ in interpreting the meanings and contexts of Prophetic traditions. The research employs a qualitative library research method using a descriptive-analytical and conceptual approach. Data were collected from classical and contemporary literature on hadith sciences, hadith commentaries (sharḥ al-ḥadīṡ), Arabic linguistics, and Islamic hermeneutics, and were analyzed through content analysis and conceptual synthesis. The findings reveal that ma’ānī al-hadīṡ is founded upon an epistemological framework that integrates linguistic, historical, social, psychological, and maqāṣid-oriented analyses, thereby enabling a more comprehensive and contextual understanding of hadith. This discipline functions not only to clarify the textual meanings of Prophetic traditions but also as a methodological instrument for bridging the normative messages of hadith with the realities of contemporary life. Therefore, strengthening the study of ma’ānī al-hadīṡ contributes significantly to the development of moderate, contextual, and relevant hadith scholarship capable of addressing contemporary Islamic issues.